Bird diversity and conservation status in KHDTK Wanadipa research forest, Universitas Diponegoro, Semarang: Ecological buffer implications for Mount Ungaran - Mochamad Lutfi Mas'ud; Fuad Muhammad; Jafron Wasiq Hidayat; Sri Puryono; Kasiyati (LPPM Universitas Negeri Jakarta, 2026)
The Wanadipa Special Purpose Forest Area (KHDTK) of Diponegoro University in Semarang provides an important refuge for wildlife amid ongoing habitat degradation in Java. This study assessed bird species, abundance, and conservation status in the educational research block and agroforestry rehabilitation zone. Surveys conducted in February 2026 using point count method at five stations recorded 133 encounters of 26 species. The most abundant were the cave swiftlet (25 individuals) and sooty-headed bulbul (17 individuals). Ecological analysis indicated a stable secondary forest ecosystem, with moderate Shannon-Wiener Diversity Index values (H’ = 2.48–2.51), low Simpson Dominance Index (D = 0.11–0.12), and high Evenness Index (E = 0.83–0.87). Five protected species were documented, including the endangered Javan hawk-eagle, alongside the crested serpent-eagle, Javan banded pitta, oriental honey-buzzard, and racquet-tailed treepie. The KHDTK Wanadipa harbors five IUCN and CITES-listed species, comparable to larger Mt. Ungaran (six species) and the Semarang urban forest (six species). These findings highlight the effectiveness of Wanadipa KHDTK as an ecological buffer supporting rare bird conservation in Semarang, Central Java.